The Analysis of Faculty Members, Peers and Self-Assessments within the Framework of PhD Qualifications by Rasch Measurement Model - Semerci, Cetin (Assoc Measurement & Evaluation Education & Psychology, 2011)
The aim of this study is to perform the analysis of faculty member, peer and self evaluation by applying Rasch model within the scope of doctorate competencies. In this study in which survey method was used, the faculty members and researchers were chosen entirely on a voluntary basis. The Rasch model has three levels. In the study, the levels comprise of 11 evaluators, 5 of whom are faculty members and 6 are postgraduate students specified in the jury, 15 competencies which are adopted by the Council of Higher Education and are criteria being currently developed and 6 postgraduate students evaulated. The study group is composed of 5 faculty members working in the division of Curriculum and Intruction as of May 2011 and 6 postgraduate students educated in this department in Firat University. According to the study findings, within the framework of determined criteria, the ones giving an outstanding performance were P1 and P2. In other words, P1 and P2 coded students were decided to be more adequate and P5 and P6 coded students were less adequate than the others. It was confirmed that J5 was the most lenient and J4 was the severest ones among the juries carrying out the evaluation. The most difficult task was B3 (taking the lead in specific and interdisciplinary studies) and the easiest task was I3 (using a language at least at C1 level taking part in The European Language Portfolio; the ability of written, oral or visual communucation at an advanced level and discussion). In this study, it was observed differences between the competencies of the postgraduate students. It is recommended that training programs for resolving these observed differences should be provided for instructors and postgraduate students.
Keywords: the scope of doctorate competencies; Rasch model; peer evaluation; self-evaluation; faculty member's evaluation